THE CONCEPT OF ECONOMIC SUSTAINABILITY - Mirkhaydarov Ismoil Mirkhoshim ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article discusses the concept of economic sustainability. The external and internal factors influencing the economic stability of the enterprise are determined. The methodology of assessment and the mechanism of management of economic stability of the enterprise is disclosed.